University, construction of social identity and development of autonomy: social representation regarding a university degree - Bustamante, Laura Andrea (2014)
This paper will report on the obtained results from our actual research project whose overall objective is to analyze the social representations of young entrants to university about college and university study. To get this objective we had been used a qualitative methodological design using as a research technique the interview on a population of admitted students at major universities in the city of Córdoba, Argentina. Data were analyzed through the constant comparative method, which allowed building a semantic mapping of the main concepts associated with the University. What is distinctive in this paper is the deepening of the category representations college degree, which has been interpreted in relation to the concept of identity. We can anticipate that the title becomes a means of identity construction of young university, and as a positive element in their independence. However, we found that the establishment of the autonomy of the young man is a budding process, which is necessary to work from the universities, since it becomes a determinant for university transit psychosocial process.